2016
DOI: 10.1016/j.chom.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Interferon Signaling Boosts Microbicidal Activity within the Tick Vector

Abstract: SUMMARY Evolution of hematophagy in blood-sucking parasites likely involves communication with their hosts. We find that Ixodes ticks are responsive to IFNγ acquired in a blood meal from mice infected with the Lyme disease-causing bacteria Borrelia burgdorferi, leading to induction of antimicrobial responses. Ixodes ticks parasitizing B. burgdorferi-infected mice up-regulated an I. scapularis Rho-like GTPase (IGTPase). IGTPase knockdown enhanced B. burgdorferi levels in post-fed ticks, suggesting this protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 28 publications
0
91
0
Order By: Relevance
“…burgdorferi , as detailed 28 . The infected ticks were fed on naïve mice (5 ticks per mouse, 3 mice per group) and fully engorged ticks were subjected to qRT-PCR analyses.…”
Section: Methodsmentioning
confidence: 99%
“…burgdorferi , as detailed 28 . The infected ticks were fed on naïve mice (5 ticks per mouse, 3 mice per group) and fully engorged ticks were subjected to qRT-PCR analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Tick salivary lectin pathway inhibitor (TSLPI) inhibits the human lectin complement pathway by interfering with the mannose binding lectin activity and enables transmission of Borrelia by protecting it from complement-mediated killing (Schuijt et al, 2011b; Wagemakers et al, 2016). Recently, Smith et al (2016) showed that I. scapularis respond to interferon gamma acquired in the blood meal when parasitizing on B. burgdorferi -infected mice, leading to the up-regulation of the Rho-like GTPase and induction of antimicrobial peptides to inhibit pathogen infection.…”
Section: Biological Processes Involved In Tick-pathogen Interactionsmentioning
confidence: 99%
“…However, the tick JAK-STAT pathway can respond to mammalian IFN-␥ imbibed with a blood meal when a pathogen is acquired from an infected mammal. This results in upregulation of antimicrobial peptides that reduce the pathogen burden in the tick (shown in the context of Borrelia burgdorferi infection of mice) (93). Vertebrate cytokines can also stimulate the mosquito midgut (94).…”
Section: Flavivirus Suppression Of Jak-stat In the Arthropod Vectormentioning
confidence: 99%